Impactos da proibição do uso de celulares sobre o cotidiano escolar e as práticas pedagógicas após a Lei n.15.100/2025: estudo de caso na rede municipal da grande Porto Alegre - (:unkn) unknown (Universidade Federal do Pampa, 2025)
This article aims to analyze the impact of the implementation of Law No. 15,100/2025, which prohibits students from using mobile phones in Brazilian public and private schools, focusing on the reality of a municipal institution in the metropolitan region. This is a qualitative, descriptive, and cross-sectional case study using semi-structured interviews, questionnaires applied to students, teachers, and school managers, and direct observation. Data were analyzed through Content Analysis methodology. The main results indicate that while most teachers noted immediate positive effects, such as increased focus and decreased distraction in the classroom, students expressed ambiguous perceptions: they understand the regulation but associate it with a punitive nature and perceive a weakened link between cell phones and formal learning. Student proposals emerged for a more balanced mediation of rules, recognizing the socio-emotional role of the device. The findings suggest that, although the prohibition favored a more disciplined environment, challenges remain for pedagogical integration of digital technologies and for building alternatives that combine innovation, discipline, and inclusion. The research reaffirms the need for more dialogic and formative strategies, involving school actors in the creation of educational policies adapted to the contemporary digital culture.
Impacts of the ban on cell phone use on daily school life and pedagogical practices after Law No. 15.100/2025: a case study in the municipal school system of Greater Porto Alegre
Keywords: Educação escolar; Proibição do celular; Mediação pedagógica; School education; Cell phone ban; Pedagogical mediation; CIENCIAS SOCIAIS APLICADAS